Effects of Nasal Continuous Positive Airway Pressure on Cerebral Hemodynamics in Preterm Infants - Zhou, Han; Hou, Xuewen; Cheng, Rui; Zhao, Youyan; Qiu, Jie (Frontiers in Pediatrics, 2020)
Background: To evaluate the effects of pressure levels on cerebral hemodynamics in premature infants receiving nasal continuous positive airway pressure (nCPAP) during the first 3 days of life. Methods: Forty-four preterm infants treated with nCPAP were divided into two groups: very preterm infants (gestational age 1 (GA1), GA<32 weeks, n=24) and moderate/late preterm infants (GA2 group, GA 32-37 weeks, n=20). During monitoring, pressure levels were set at 4→6→8→4 cmH2O, and cerebral hemodynamics was assessed by near-infrared spectroscopy (NIRS). Vital signs, peripheral oxygen saturation (SpO2) and transcutaneous carbon dioxide pressure (TcPCO2) were simultaneously recorded. Results: Pressures of 4-8 cmH2O had no significant influence on cerebral hemodynamics, vital signs, SpO2 or TcPCO2. The tissue oxygenation index (TOI), the difference between oxygenated hemoglobin (△HbO2) and deoxygenated hemoglobin (△HHb) (△HbD), and cerebral blood volume (△CBV) were all significantly positively correlated with gestational and postnatal age, with fluctuations being greater in the GA1 group. △HbD and △CBV were also significantly positively correlated with TcPCO2. Conclusions: No significant differences were observed in cerebral hemodynamics when the nCPAP pressure was set to 4 to 8 cmH2O.